Engaging with immigrant students' voices in the school environment: an analysis of policy documents through school websites - Maritta Välimäki; Kirsi Hipp; Faye Acton; Angelika Echsel; Ioan-Alexandru Grădinaru; Katrin Hahn-Laudenberg; Christina Schulze; Elisabeth Stefanek; Georg Spiel; Niamh O'Brien (BMC, 2024)
Abstract Background For students to feel happy and supported in school, it is important that their views are taken seriously and integrated into school policies. However, limited information is available how the voices of immigrant students are considered in European school contexts. This study generated evidence from written documents to ascertain how student voice practices are described at school websites. Methods Between 2 March and 8 April 2021, we reviewed the policy documents publicly available on school websites. The schools located in areas of high immigration in six European countries: Austria, England, Finland, Germany, Romania, and Switzerland. The READ approach was used to guide the steps in the document analysis in the context of policy studies (1) ready the materials, 2) data extraction, 3) data analysis, 4) distil the findings). A combination of qualitative and quantitative approaches with descriptive statistics (n, %, Mean, SD, range) was used for analysis. Results A total of 412 documents (305 schools) were extracted. Based on reviewing school websites, reviewers'strongly agreed' in seven documents (2%) that information related to seeking student voices could be easily found. On the contrary, in 247 documents (60%), reviewers strongly indicated that information related to seeking student voices was missing. No clear characteristics could be specified to identify those schools were hearing students' voices is well documented. The most common documents including statements related to student voice were anti-bullying or violence prevention strategies (75/412) and mission statements (72/412). Conclusions Our document analysis based on publicly accessible school websites suggest that student voices are less frequently described in school written policy documents. Our findings provide a baseline to further monitor activities, not only at school level but also to any governmental and local authorities whose intention is to serve the public and openly share their values and practices with community members. A deeper understanding is further needed about how listening to student voices is realized in daily school practices.